2007
DOI: 10.1038/bdj.2007.779
|View full text |Cite
|
Sign up to set email alerts
|

The perceived barriers of vocational dental practitioners in London to specialisation

Abstract: Objective To investigate the short-and long-term career aspirations and barriers to postgraduate study of recently qualifi ed vocational dental practitioners (VDPs). Method One hundred and eight vocational dental practitioners in London were asked to complete a questionnaire survey. Results The questionnaires were completed by 94 respondents (85%) and results indicated that the majority of the VDPs wanted to continue to work in general dental practice after vocational training (VT). Nearly 80% of the VDPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 5 publications
4
10
2
Order By: Relevance
“…A recent study found that a large proportion (71%) of UK undergraduates expressed a desire to specialise following graduation, with Orthodontics being the most popular intended specialty [ 3 ]. This supports an earlier UK study which found that 83% of recent graduates were either ‘certain of’ or ‘considering’ pursuing a specialist career, [ 4 ] although for this group of young dentists, Restorative dentistry was the most preferred intended pathway. For these recent graduates, the ‘length of training’, ‘cost’ and ‘disruption of life’ were reported to be the three greatest barriers to further specialisation.…”
Section: Introductionsupporting
confidence: 85%
“…A recent study found that a large proportion (71%) of UK undergraduates expressed a desire to specialise following graduation, with Orthodontics being the most popular intended specialty [ 3 ]. This supports an earlier UK study which found that 83% of recent graduates were either ‘certain of’ or ‘considering’ pursuing a specialist career, [ 4 ] although for this group of young dentists, Restorative dentistry was the most preferred intended pathway. For these recent graduates, the ‘length of training’, ‘cost’ and ‘disruption of life’ were reported to be the three greatest barriers to further specialisation.…”
Section: Introductionsupporting
confidence: 85%
“…Even though gender is a controversial determinant in choosing specialty (Fisher, Wilson, & Bartlett, 2007;Scarbecz & Ross, 2007;Dhima, Petropoulos, Han, Kinnunen, & Wright, 2012), the present study found gender with an impact on the choice of some specialties. This agrees with other reports (Karibe, Suzuki, Sekimoto, Srithavaj, Iamaroon, Warita, Kawakami, Ogata, Shirase, & Nakahara, 2007) where males were more likely to advance into an Oral and Maxillofacial Surgery field, whereas females were more interested in Paediatric Dentistry.…”
Section: Discussioncontrasting
confidence: 48%
“…The findings seem to be related to each country realities, politic and the time's context of the study. In UK 83% of graduate's dental student's preferred Restorative dentistry as the most intended specialty (Fisher, Wilson, & Bartlett, 2007), while nine years later, 71% of dental students of the same institution expressed to specialize with Orthodontics specialty (James, Veselina, & Alisa, 2016). Studies views of Japanese, Canadian and Thai undergraduates found that Orthodontics was the most preferred subject in the first two countries, and Oral Surgery in the latter country (Karibe, Suzuki, Sekimoto, Srithavaj, Iamaroon, Warita, Kawakami, Ogata, Shirase, & Nakahara, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations